Tucker's countryside - Selden, George, 1929-1989; Williams, Garth (New York : Square Fish, 2012)
Harry Cat and Tucker Mouse, both of New York City, go to visit Chester Cricket at the Old Meadow in Connecticut.
Originally published: New York : Farrar, Straus and Giroux, 1969.
Keywords: Cats -- Fiction; Mice -- Fiction; Crickets -- Fiction; Country life -- Fiction; Animals -- Fiction